Efficacy and safety of pegylated‐interferon α‐2a in myelofibrosis: a study by the FIM and GEM French cooperative groups. (13th July 2013) - Ianotto, Jean‐Christophe; Boyer‐Perrard, Françoise; Gyan, Emmanuel; Laribi, Kamel; Cony‐Makhoul, Pascale; Demory, Jean‐Loup; De Renzis, Benoit; Dosquet, Christine; Rey, Jerome; Roy, Lydia; Dupriez, Brigitte; Knoops, Laurent; et al.
Summary: Myeloproliferative neoplasm‐related myelofibrosis is associated with cytopenic or proliferative phases, splenomegaly and constitutional symptoms. Few effective treatments are available and small series suggested that interferon could be an option for myelofibrosis therapy. We performed a retrospective study of pegylated‐interferon α‐2a (Peg‐IFNα‐2a) therapy in myelofibrosis. Sixty‐two patients treated with Peg‐IFNα‐2a at 17 French and Belgian centres were included. Responses were determined based on the criteria established by the International Working Group for Myelofibrosis Research and Treatment. Mean follow‐up was 26 months. Sixteen of 25 anaemic patients (64%) (eight concomitantly receiving recombinant erythropoietin) achieved a complete response and transfusion‐independence was obtained in 5/13 patients (38·5%). Constitutional symptoms resolved in 82% of patients. All five leucopenic patients normalized their leucocyte counts, whereas a normal platelet count was obtained in 5/8 thrombocytopenic patients. Splenomegaly was reduced in 46·5% of patients, and complete resolution of thrombocytosis and leucocytosis were observed in 82·8% and 68·8% of patients, respectively. Side effects (mostly haematological) were mainly of grade 1–2. The only factor independently associated with treatment failure was a spleen enlargement of more than 6 cm below the costal margin. In conclusion, Peg‐IFNα‐2a induced high response rates with acceptable toxicity in a large proportion of patients with primary and secondary myelofibrosis, especially in early phases.